2005
DOI: 10.4103/0019-5545.55939
|View full text |Cite
|
Sign up to set email alerts
|

Group meetings of caretakers of patients with schizophrenia and bipolar mood disorders

Abstract: Background:In India, there is a paucity of trained professionals to execute psychosocial interventions. Families are thus assigned the role of primary caretakers of individuals with chronic mental illness.Aim:To assess the perceived benefits and difficulties of group meetings among caregivers of persons with schizophrenia and bipolar mood disorders, and to evaluate the utilization pattern of general hospital psychiatric unit (GHPU) services by caregivers who regularly attend such group meetings.Methods:Persons… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
14
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(14 citation statements)
references
References 4 publications
0
14
0
Order By: Relevance
“…5 Other studies had also found similar results. 6,17 Maximum percentage of the caretakers in this study i.e. 60% were Hindus whereas 27.5% were Muslims and 12.5% were of other religion.…”
Section: Discussionmentioning
confidence: 63%
“…5 Other studies had also found similar results. 6,17 Maximum percentage of the caretakers in this study i.e. 60% were Hindus whereas 27.5% were Muslims and 12.5% were of other religion.…”
Section: Discussionmentioning
confidence: 63%
“…Support groups can fulfill the needs of the siblings and alleviate their issues in caring for a sibling with psychosis. Empirical results show that such groups on caregivers of psychosis were found to be effective in addressing various issues and needs 42,43,44,45,46)…”
Section: Discussionmentioning
confidence: 99%
“…Family intervention: Many studies have evaluated the efficacy and effectiveness of family intervention in schizophrenia (Chacko 1967;Narayanan et al 1972Narayanan et al , 1988Pai and Kapur 1983;Pai and Roberts 1983;Pai et al 1985;Verghese 1988;Ismail Shihabuddeen and Gopinath 2005;Thara et al 2005;Kulhara et al 2009;Sovani 1993;Devaramane et al 2011;Patra et al 2011). These studies have used different kinds of interventions such as home-based treatment by nurse, treatment in the family ward, family psychoeducation, brief inpatient intervention and single-session psychoeducation.…”
Section: Caregivers' Issuesmentioning
confidence: 99%
“…These studies reflect that family psychoeducation for schizophrenia (addressing optimal medication management and addressing the family's feelings of loss) leads to reduction in the rates of relapse, which is significantly more than that seen in the control groups. Benefits are also noted in the form of reduction in burden, functioning, symptom reduction, rate of hospitalization, knowledge and attitude, use of better coping skills, treatment adherence, drug compliance, disability, caregiver satisfaction and caregiver support (Chacko 1967;Narayanan et al 1972Narayanan et al , 1988Pai and Kapur 1983;Pai and Roberts 1983;Pai et al 1985;Verghese 1988;Ismail Shihabuddeen and Gopinath 2005;Thara et al 2005;Kulhara et al 2009;Sovani 1993;Devaramane et al 2011). …”
Section: Caregivers' Issuesmentioning
confidence: 99%